2017
DOI: 10.1155/2017/4130824
|View full text |Cite
|
Sign up to set email alerts
|

Amifostine Pretreatment Attenuates Myocardial Ischemia/Reperfusion Injury by Inhibiting Apoptosis and Oxidative Stress

Abstract: The present study was aimed at investigating the effect of amifostine on myocardial ischemia/reperfusion (I/R) injury of mice and H9c2 cells cultured with TBHP (tert-butyl hydroperoxide). The results showed that pretreatment with amifostine significantly attenuated cell apoptosis and death, accompanied by decreased reactive oxygen species (ROS) production and lower mitochondrial potential (ΔΨm). In vivo, amifostine pretreatment alleviated I/R injury and decreased myocardial apoptosis and infarct area, which wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 31 publications
1
23
0
Order By: Relevance
“…In the current study, we found activation of ROS and MAPKs signaling in heart of I/R mice, suggesting the involvement of ROS and MAPKs in cardiac I/R injury. Indeed, our in vivo and in vitro data showed that both ROS and MAPKs mediated I/R- and A/R-induced cardiomyocyte apoptosis, because pharmacological inhibition of ROS or MAPKs almost completely abolished the increase in apoptotic cell population, in line with the important roles of ROS and MAPKs in regulating apoptotic heart cell death [23, 24, 35]. Since ROS and MAPKs seem to be involved in the same signaling pathway, we proceeded to test the sequence of ROS and MAPKs.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…In the current study, we found activation of ROS and MAPKs signaling in heart of I/R mice, suggesting the involvement of ROS and MAPKs in cardiac I/R injury. Indeed, our in vivo and in vitro data showed that both ROS and MAPKs mediated I/R- and A/R-induced cardiomyocyte apoptosis, because pharmacological inhibition of ROS or MAPKs almost completely abolished the increase in apoptotic cell population, in line with the important roles of ROS and MAPKs in regulating apoptotic heart cell death [23, 24, 35]. Since ROS and MAPKs seem to be involved in the same signaling pathway, we proceeded to test the sequence of ROS and MAPKs.…”
Section: Discussionmentioning
confidence: 81%
“…Since both ROS and MAPKs have been considered important mediators of cell apoptosis [23-25], we initially investigated the effect I/R injury on these pathways activation in cardiomyocytes. H 2 DCF-DA staining showed that the ROS production in heart slices from I/R mice was dramatically increased as compared with sham mice (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Myocardial I/R injury is a complex pathophysiological process associated with a variety of mechanisms, including oxidative stress, cell apoptosis and inflammatory responses (5)(6)(7). The particular mechanisms underlying the development of myocardial I/R injury are unclear; however, it has been reported that excessive production of reactive oxygen species (ROS) is a primary factor that activates a variety of molecular cascades of apoptosis, thereby aggravating myocardial I/R injury (8,9). Therefore, inhibition of ROS production or the scavenging of free radicals may be potential therapeutic strategy to attenuate I/R injury.…”
Section: Introductionmentioning
confidence: 99%
“…7) Therefore, antioxidant agents have been proposed to treat myocardial ischemia reperfusion. 8) Hydrogen peroxide (H2O2), as an exogenous ROS, could activate caspase-3 and subsequently activates the mitochondria-dependent pathway. 9) However, it is not clear whether H2O2 affects the expression of miR-208a.…”
mentioning
confidence: 99%